Silibinin inhibits ultraviolet B radiation-induced mast cells recruitment and bone morphogenetic protein 2 expression in skin at early stages in Ptch(+/−) mouse model of basal cell carcinoma - Rigby, Cindy (Mol Carcinog, 2019)
Around 80% of non-melanoma skin cancers (NMSCs) are basal cell carcinoma (BCC), still studies evaluating the efficacy of chemopreventive agents during early stage/s of BCC development are lacking. Accordingly, utilizing the well-established patched (Ptch)+/− mouse model of ultraviolet B (UVB) radiation-induced BCC formation, we excised skin samples from UVB exposed Ptch+/− and Ptch+/+ mice prior to tumor formation to study the promotion/ progression of BCC and to determine the efficacy and target/s of silibinin, a well-known skin cancer chemopreventive agent. UVB exposure for 1 month increased the number of mast cells in Ptch+/− mice by ~48% (P<0.05), which was completely inhibited by silibinin. PCR profiler array analysis of skin samples showed strong molecular differences between Ptch+/+ and Ptch+/− mice which were either unexposed or UVB irradiated +/−silibinin treatment. Most notably, silibinin treatment significant decreased the expression of BMP-2, Bbc3, PUMA and Ccnd1 in Ptch+/− mice irradiated with silibinin + UVB. Additional studies showed that silibinin targets UVB-induced expression of BMP-2 in Ptch+/− mouse skin. Lastly, our studies found that silibinin strongly attenuates UVB-induced BMP-2 expression and DNA damage in Ptch+/− mouse skin ex vivo only after single UVB exposure. Together, our results suggest a possible role of mast cell recruitment and BMP-2 activation in the early stages of BCC development; these are strongly inhibited by silibinin suggesting its possible chemopreventive efficacy against BCC formation in long-term UVB exposure regimen.